2016
DOI: 10.1021/acs.jafc.6b03588
|View full text |Cite
|
Sign up to set email alerts
|

Increased Production of Food-Grade d-Tagatose from d-Galactose by Permeabilized and Immobilized Cells of Corynebacterium glutamicum, a GRAS Host, Expressing d-Galactose Isomerase from Geobacillus thermodenitrificans

Abstract: The generally recognized as safe microorganism Corynebacterium glutamicum expressing Geobacillus thermodenitrificans d-galactose isomerase (d-GaI) was an efficient host for the production of d-tagatose, a functional sweetener. The d-tagatose production at 500 g/L d-galactose by the host was 1.4-fold higher than that by Escherichia coli expressing d-GaI. The d-tagatose-producing activity of permeabilized C. glutamicum (PCG) cells treated with 1% (w/v) Triton X-100 was 2.1-fold higher than that of untreated cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…However, immobilized cells for D ‐allulose production have not been reported yet. Previous study reported the research on D ‐tagatose production using immobilized cells of recombinant C. glutamicum expressing D ‐galactose isomerase (Shin, Sim, Seo, & Oh, ). In this study, we attempted to prepare immobilized cells of DAE16 and INV1 using alginate as carrier and measure their catalytic efficiency in conversion of fructose and sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…However, immobilized cells for D ‐allulose production have not been reported yet. Previous study reported the research on D ‐tagatose production using immobilized cells of recombinant C. glutamicum expressing D ‐galactose isomerase (Shin, Sim, Seo, & Oh, ). In this study, we attempted to prepare immobilized cells of DAE16 and INV1 using alginate as carrier and measure their catalytic efficiency in conversion of fructose and sucrose.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cytosolic protein expression in C. glutamicum has contributed to the production of biochemicals such as polyhydroxyalkanoate (PHA) (Matsumoto et al, 2011 ), ethanol (Jojima et al, 2015 ), and γ-aminobutyric acid (GABA) (Choi et al, 2015 ). The industrial techniques for the production of rare saccharides such as D-tagatose (Shin et al, 2016 ), D-sorbose and D-psicose (Yang et al, 2015 ), D-allose ( https://patents.google.com/patent/WO2017111339A1/en ), and GDP-L-fucose (Chin et al, 2013 ) are also the methods of nutraceutical production that involve cytosolic protein overexpression in C. glutamicum .…”
Section: Cytosolic Protein Expression In C Glutamicum mentioning
confidence: 99%
“…Corynebacterium glutamicum , a gram-positive bacterium with a high G+C content, has been used for the industrial production of various amino acids for more than 50 years. Moreover, it has recently demonstrated strong potential for use as a protein expression system [ 1 , 2 ] because of its excellent culture characteristics and also because it is non-pathogenic, does not produce endotoxins, and is generally recognized as safe [ 3 , 4 ]. Furthermore, C. glutamicum produces minimal protease activity in the culture supernatant and has the ability to secrete properly folded proteins, which can improve subsequent purification efficiency.…”
Section: Introductionmentioning
confidence: 99%